De novo 14q24.2q24.3 microdeletion including IFT43 is associated with intellectual disability, skeletal anomalies, cardiac anomalies, and myopia. Issue 6 (19th February 2016) - Stokman, Marijn F.; Oud, Machteld M.; van Binsbergen, Ellen; Slaats, Gisela G.; Nicolaou, Nayia; Renkema, Kirsten Y.; Nijman, Isaac J.; Roepman, Ronald; Giles, Rachel H.; Arts, Heleen H.; Knoers, Nine V. A. M.; van Haelst, Mieke M.
Abstract : We report an 11‐year‐old girl with mild intellectual disability, skeletal anomalies, congenital heart defect, myopia, and facial dysmorphisms including an extra incisor, cup‐shaped ears, and a preauricular skin tag. Array comparative genomic hybridization analysis identified a de novo 4.5‐Mb microdeletion on chromosome 14q24.2q24.3. The deleted region and phenotype partially overlap with previously reported patients. Here, we provide an overview of the literature on 14q24 microdeletions and further delineate the associated phenotype. We performed exome sequencing to examine other causes for the phenotype and queried genes present in the 14q24.2q24.3 microdeletion that are associated with recessive disease for variants in the non‐deleted allele. The deleted region contains 65 protein‐coding genes, including the ciliary gene IFT 43. Although Sanger and exome sequencing did not identify variants in the second IFT43 allele or in other IFT complex A‐protein‐encoding genes, immunocytochemistry showed increased accumulation of IFT‐B proteins at the ciliary tip in patient‐derived fibroblasts compared to control cells, demonstrating defective retrograde ciliary transport. This could suggest a ciliary defect in the pathogenesis of this disorder. © 2016 Wiley Periodicals, Inc.